(untitled) (Research, Society and Development, 2022)
The objective was to reflect on the approaches applied within the multidisciplinary consultation facing the sexuality of the LGBTQIA+ population. This is an integrative literature review, through a search within the databases: Database in Nursing, Latin American Caribbean Literature in Health Sciences and Medical Literature Analysis and Retrieval System Online. Among the inclusion criteria: addressed the central theme of the study, published between 2016 to 2021 and in Portuguese, English and/or Spanish. Obtaining the totality of 7 documents. The population’s access is mainly through the Basic Health Units (UBS) through the Family Health Strategy. Within these units, professionals in nursing, medicine, physiotherapy, nutrition, dentistry, social work, among others, perform various functions, including your consultation, that is, they will be in direct contact with the LGBTQIA+ public. It is concluded that the world has been evolving in all aspects, however, there is still a strong social stigma that enters people’s lives and ends up generating prejudice, whether this is veiled or not. This discrimination is also present within health units and consultations provided by the multidisciplinary health team.